2013
DOI: 10.1007/s00024-013-0710-x
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Density Analysis for Wave Characteristics in Pohang New Harbor

Abstract: Abstract-The Pohang New Harbor (PNH), located at the Yongil bay in the northeastern part of Pohang city, South Korea, has experienced extreme wave hazards of about 3.0-5.0 m in elevation due to the seasonal swell from the far ocean. In this paper, both analytical and numerical studies are performed to investigate the wave-induced oscillations in an arbitrary shaped harbor with corner point consideration. By taking the consideration of the actual topography and bathymetry data, the boundary of PNH is constructe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 16 publications
3
6
0
Order By: Relevance
“…Gonz谩 lez-Marco et al (2008) analyzed the effect of IG waves on port operations in Gij贸n harbor (Spain) and found that the port's inefficiency is significantly increased if IG waves are present in the wave trains, although the harbor offers very good protection against wind short waves. Similar situations can be found in various other ports and harbors around the world, such as Hua-Lien harbor in Taiwan (Chen et al, 2004), Hosojima harbor in Japan (Yoshida et al, 2000), Port of Long Beach in California (Kofoed-Hansen et al, 2005), and Pohang New Harbor in South Korea (Kumar et al, 2014). Hence, in order to identify layouts and technical solutions that minimize the downtime of the facility, it is crucial to further improve the knowledge of the IG waves inside the harbor.…”
Section: Introductionsupporting
confidence: 63%
“…Gonz谩 lez-Marco et al (2008) analyzed the effect of IG waves on port operations in Gij贸n harbor (Spain) and found that the port's inefficiency is significantly increased if IG waves are present in the wave trains, although the harbor offers very good protection against wind short waves. Similar situations can be found in various other ports and harbors around the world, such as Hua-Lien harbor in Taiwan (Chen et al, 2004), Hosojima harbor in Japan (Yoshida et al, 2000), Port of Long Beach in California (Kofoed-Hansen et al, 2005), and Pohang New Harbor in South Korea (Kumar et al, 2014). Hence, in order to identify layouts and technical solutions that minimize the downtime of the facility, it is crucial to further improve the knowledge of the IG waves inside the harbor.…”
Section: Introductionsupporting
confidence: 63%
“…Gonz谩 lez-Marco et al (2008) investigated the effect of IG waves on port operations in Gij贸n harbor (Spain) and found that if IG waves are present in the wave trains, the port's inefficiency is significantly increased although the harbor offers very good protection against wind short waves. Similar situations can be also found in other ports and harbors around the world, such as the Marina di Carrara harbor in Italy (Guerrini et al, 2014), Two Rocks Marina in Australia (Thotagamuwage and Pattiaratchi, 2014a, b), Hosojima harbor in Japan (Yoshida et al, 2000), Hua-Lien harbor in Taiwan (Chen et al, 2004), Pohang New Harbor in South Korea (Kumar et al, 2014) and Port of Long Beach in California (Kofoed-Hansen et al, 2005). Therefore, to identify layouts and technical solutions that minimize the downtime of the facility, it is vital to further improve the knowledge of the IG waves inside the harbor.…”
Section: Introductionsupporting
confidence: 56%
“…This phenomenon may lead to excessive responses of berthing vessels, which would significantly interrupt the loading/unloading operations of the ships and even break mooring lines and cause collision accidents (Kumar et al, 2016;Gulshan et al, 2020). Innumerous harbors all over the world have observed the phenomenon, such as Longkou Harbor (Wang et al, 1987), Hualien Harbor (Maa et al, 2011), Long Beach Harbor (Lee and Xing, 2009), Pohang Harbor (Kumar and Rupali, 2018;Kumar et al, 2014), Hambantota Port (Dong et al, 2020b) and Paradip Port (Rupali et al, 2020a, b), and huge economic losses and even casualties have been caused.…”
Section: Introductionmentioning
confidence: 99%